EFFECTS OF MASTERY LEARNING STRATEGY ON MATHEMATICAL COMPETENCE AMONG SECONDARY SCHOOL STUDENTS IN MACHAKOS COUNTY, KENYA - MULUNGYE, MARY MBATHE (MksU Press, 2023)
Despite the fact that Mathematics is considered as a vital subject that supports the development of critical and logical thinking., majority of students across the world dislike mathematics and stay away from many careers related to Mathematics. The students’ lack of interest for mathematics could be attributed to poor quality of instruction and the instructional method deployed but not lack of ability to learn. The purpose of the study was to establish the effect of Mastery Learning Strategy on Mathematical Competence among Secondary School Students in Machakos SubCounty Kenya. The study was guided by four objectives: to investigate the impact of mastery learning strategy on students’ competence on a Mathematical test; to investigate the impact of mastery learning strategy on students’ attitude towards Mathematics; to investigate the impact of mastery learning strategy on students’ level of errors and misconceptions committed in Mathematics and to investigate the impact of mastery learning strategy on students’ level of self-efficacy when solving a Mathematics problem. Two co-educational Schools were randomly sampled, then using the Solomon’s FOUR randomized Group Design, two Form two streams were randomly selected from each school and randomly assigned to Experimental Group and the Control Group respectively. A pretest was given before the intervention. The Experimental group was taught using Mastery Learning Strategy (MLS), while the Control group was taught using Conventional Group Learning (CGL). The research used a competence test, an attitudinal test towards Mathematics, errors and misconception in Algebra assessment test and the level of self-efficacy test. The Analysis of Variance (ANOVA), indicated that the mean score difference for all the groups was significant at  = 0.05 as evident by the Fishers ratio and p-value. A ChiSquare analysis revealed that there was a strong association between the use of MLS and the quality of competence in Mathematics. The computed z score value of |- 2.72|was greater than the critical value of z = 1.96 at 5% level of significance, therefore the proportion difference between the two groups was statistically significant. It was noted that the use of MLS had a statistically insignificant effect on Mathematical concept errors, the conceptual understanding errors and the word Mathematical problem errors. It was established that the Gender of the learners did not have an effect on the learning outcomes resulting from use of MLS. MLS was recommended for improved competence performance, changed attitude towards Mathematics, and a sure strategy to boost the morale and self-efficacy among the students. Therefore, the study recommends that teachers and learners should be exposed to MLS to help break the cycle of failure in Mathematics. The study also recommends a replication of the research for other topics in Mathematics; another region and different respondents to ascertain the validity and reliability of the findings. It was concluded that MLS is an effective teaching strategy that can bring a positive change in the learning of Mathematics, attitude towards Mathematics and on self-efficacy.